P062 Non-pharmacological interventions for sleep problems in neuro-typical children: a systematic review. (19th November 2019) - Turton, Clarice; Hamilton, Anna; Weighall, Anna; Kellar, Ian
Abstract : Context: Sleep disturbances and disorders are common in children. Non-pharmacological interventions for such disorders are recommended by current guidelines. Recent reviews important in this area focus solely on children with neurodevelopmental disorders (Scantlebury et al., 2018). The current review seeks to synthesise the evidence for children in the the non-clinical population. Objective: To expand upon recent reviews by reviewing non-pharmacological interventions for sleep problems in neuro-typical children. Data Sources: Five electronic databases (MEDLINE, EMBASE, PsycINFO, CINAHL and Cochrane databases) were searched using search terms including and relating to 'Children', 'Sleep', 'Behavioural Interventions' and 'Randomised Control Trials'. Study selection: Randomised control trials using non-pharmacological interventions with a sleep outcome, for children and adolescents over five years old were included in the study. Synthesis. Results were synthesised narratively in relation to intervention content, delivery and efficacy. Conclusions: The studies overall support the recommendation of using non-pharmacological interventions for sleep problems in children. The majority of research to date has investigated the efficacy of cognitive behavioural techniques and was found to be effective in a clinical setting. Future research should evaluate the feasibility and efficacy of these techniques applied on a wider scale and in home settings in order to reach more children.